The effect of a proposed training program to improve the explosive power of 19U handball players study on Al-Wefaq Sports Team for the Municipality of Drahi, Salah Salah ESDB, Mila - heddouche, aissa; maalem, Abed Elmalek; boussaadia, toufik (sports creativity, 2025)
The study aims to know the effect of a proposed training program to improve the explosive power of the U19 Cuban handball players. Field study on Al Wifaq Sports Team for the municipality of Drahi, Salahah, ESDB, Mila. A training program with a set of physical tests was applied to them as a way to determine the degree of differences. The researcher also used the statistical assertion spss 20 to analyze and read the results. The results came according to the proposed hypotheses, meaning that there are statistically significant differences due to the proposed training program H in favor of dimensional measurement The researcher has recommended diversification in training methods for developing the explosive strength characteristic of players, as well as allocating a suitable weekly hourly size to it.